calculeaza
60+4x[36:9+3x(20+8x42:4)]=
Răspunsuri la întrebare
Răspuns de
2
60+4x[36:9+3x(20+8x42:4)]=
60+4x[36:9+3x(20+336:4)]=
60+4x[36:9+3x(20+84)]=
60+4x(36:9+3x104)=
60+4x(4+312)=
60+4x316=
60+1264=
1324
60+4x[36:9+3x(20+336:4)]=
60+4x[36:9+3x(20+84)]=
60+4x(36:9+3x104)=
60+4x(4+312)=
60+4x316=
60+1264=
1324
patrypatricia46:
iti va da 1324
Răspuns de
0
60+4x[36:9+3x(20+8x42:4)]=
60+4x[36:9+3x(20+336:4)]=
60+4x[36:9+3x(20+84)]=
60+4x(36:9+3x104)=
60+4x(4+312)=
60+4x316=
60+1 264=
1324
60+4x[36:9+3x(20+336:4)]=
60+4x[36:9+3x(20+84)]=
60+4x(36:9+3x104)=
60+4x(4+312)=
60+4x316=
60+1 264=
1324
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
10 ani în urmă
Limba română,
10 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă